2021
DOI: 10.15252/embr.202152963
|View full text |Cite
|
Sign up to set email alerts
|

Intertissue mechanical interactions shape the olfactory circuit in zebrafish

Abstract: In zebrafish embryos, eye morphogenesis steers neuronal movements and axon extension in the overlying olfactory placode by exerting traction forces in the lateral direction, transmitted to the placode through extracellular matrix.• The cell bodies of olfactory placode neurons and cells in the adjacent eye tissue undergo highly correlated morphogenetic movements in the mediolateral direction, suggesting an interaction between the two tissues.• In mutants lacking eyes, mechanical stress at the lateral border of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Consequently, when the optic cup does not form in eyeless rx3 mutant embryos, placode movements are reduced, and axons are shorter and less stretched. 69 Thus, pioneer axon elongation is mediated by mechanical forces but not by guidance or trophic molecules. While these findings have not been confirmed in other species, these movements could also explain pioneer olfactory axon formation in mammals and humans.…”
Section: Innervation Of the Olfactory Systemmentioning
confidence: 99%
“…Consequently, when the optic cup does not form in eyeless rx3 mutant embryos, placode movements are reduced, and axons are shorter and less stretched. 69 Thus, pioneer axon elongation is mediated by mechanical forces but not by guidance or trophic molecules. While these findings have not been confirmed in other species, these movements could also explain pioneer olfactory axon formation in mammals and humans.…”
Section: Innervation Of the Olfactory Systemmentioning
confidence: 99%
“…To perturb the organisation of the rosette, we manipulated the early coalescence of the olfactory placodes, during which morphogenetic cell movements transform two elongated placodal cell fields lying on each side of the brain into spherical neuronal clusters (Breau et al, 2017; Aguillon et al, 2020; Monnot et al, 2022). We reasoned that perturbing the morphogenesis of the olfactory placode at these early stages (12-22 hpf) would likely result in abnormal rosette formation at our stages of interest (26-34 hpf).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is related information, these questions have not been systematically addressed. A recent interesting study has shown that the extensive evagination and invagination movements of the zebrafish eye exert traction forces on the adjacent olfactory placode, influencing its development ( Monnot et al, 2022 ). Does the opposite hold true?…”
Section: Discussionmentioning
confidence: 99%